Bahasa Gaul di Kalangan Remaja Kota Medan, Tantangan dalam Pembinaan Bahasa Baku - Elza L. Saragih; Samuel Banjarnahor; Kartina Siagian; Lasro Jumanta Sihite (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The use of slang among teenagers in Medan City has become a compelling social phenomenon to study. Slang, which tends to be informal and expressive, now dominates the communication patterns of youth, even in contexts that should require the use of standard language. This research aims to describe the forms of slang used by teenagers, identify the challenges in fostering standard language, and propose strategies to harmonize the use of slang and standard Indonesian. The method used in this study includes literature review and simple observations of teenagers' daily language use in Medan. The results show that slang serves as a means of expressing identity and group solidarity but also raises concerns about the decline in the ability to use proper and correct Indonesian. The main challenges include the dominance of social media, lack of role models in standard language use, and low motivation among youth to use formal language. Therefore, innovative and communicative strategies are needed so that the younger generation can shift language contexts appropriately without abandoning the richness of standard Indonesian.